2005
DOI: 10.1089/end.2005.19.894
|View full text |Cite
|
Sign up to set email alerts
|

Load-Release Points of Two Novel Ureteral Stone-Trapping Devices

Abstract: Both of the devices released the plastic bead reliably and at low loads, although the NTrap did require statistically significantly more force than the Stone Cone. However, the loads for both devices were <1 lb, so the devices are unlikely to result in ureteral trauma. Whether a slight increase in load-release force or differences in design result in better stone-clearing ability of one device should be assessed in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The two novel devices (Stone Cone and NTrap®) have been previously tested and compared for pull-through strength, which is the force required for each device to deploy and release the beads in a strictured ureter model. Ouwenga et al reported statistically significant but clinically insignificant differences in the releasing force of the two devices [17]. The Stone Cone showed a pull-through strength of 0.190 lbf and the NTrap® device showed a strength of 0.861 lbf, which the group believed was presumably too low to result in ureteral avulsion.…”
Section: Discussionmentioning
confidence: 99%
“…The two novel devices (Stone Cone and NTrap®) have been previously tested and compared for pull-through strength, which is the force required for each device to deploy and release the beads in a strictured ureter model. Ouwenga et al reported statistically significant but clinically insignificant differences in the releasing force of the two devices [17]. The Stone Cone showed a pull-through strength of 0.190 lbf and the NTrap® device showed a strength of 0.861 lbf, which the group believed was presumably too low to result in ureteral avulsion.…”
Section: Discussionmentioning
confidence: 99%